2011
DOI: 10.1002/bjs.7229
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative assessment of sentinel lymph nodes in breast cancer

Abstract: Background: Sentinel lymph node biopsy (SLNB) reduces the morbidity of axillary clearance and is the standard of care for patients with clinically node-negative breast cancer. The ability to analyse the sentinel node during surgery enables a decision to be made whether to proceed to full axillary clearance during primary surgery, thus avoiding a second procedure in node-positive patients.Methods: Current evidence for intraoperative sentinel node analysis following SLNB in breast cancer was reviewed and evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
71
2
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 73 publications
1
71
2
8
Order By: Relevance
“…Many studies have already shown that FS does not allow for accurate diagnosis in all cases, since its high specificity does not associate with high sensitivity [19,20]. OSNA is a relatively recent technique that detects mRNA expression of epithelial breast cancer marker cytokeratine 19 (CK19) in the biopsied lymph node.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have already shown that FS does not allow for accurate diagnosis in all cases, since its high specificity does not associate with high sensitivity [19,20]. OSNA is a relatively recent technique that detects mRNA expression of epithelial breast cancer marker cytokeratine 19 (CK19) in the biopsied lymph node.…”
Section: Discussionmentioning
confidence: 99%
“…However, the procedure is expensive, labor intensive, time-consuming and operator dependent. Besides, FS determines an irreversible tissue loss due to cryostat processing, causing a more difficult and inaccurate detection of micro-and sometimes even macrometastatic involvement at routine histopathology [19]. As far as costs are concerned, FS is at least three times more expensive than TIC, considering that the cost of evaluating two SLNs using TIC is 131$ compared to 356$ for FS [27].…”
Section: Discussionmentioning
confidence: 99%
“…These results are reasonable, because 2 mm-section histology can miss metastases <2 mm between the cut surfaces, and the falsenegative rate of intraoperative FS histology, mainly resulting from failure to detect micrometastases, has been found to range from approximately 30% to 40% compared with the final pathological results. 9 The OSNA assay could detect more sentinel lymph node metastases than could FS histology from primary tumors without lymphovascular or fat invasion, or from microinvasive tumors. Several studies have shown that primary tumors with nodal micrometastases are smaller than those with macrometastases.…”
Section: Discussionmentioning
confidence: 99%
“…However, the false-negative rate of FS histology, mainly resulting from failure to detect micrometastases, have been found to range from 26% to 43% compared with the final pathological results. 9 The one-step nucleic acid amplification (OSNA) assay (Sysmex, Kobe, Japan) is a rapid molecular detection procedure that analyses lymph node metastases by detection and amplification of cytokeratin 19 (CK19) mRNA. 10 This assay could accurately detect clinically relevant nodal metastases of >0.2 mm at rates comparable to conventional pathological examination, in at least half of the lymph nodes tested.…”
mentioning
confidence: 99%
“…These include frozen section analysis, touch imprint cytology and molecular analysis. The sensitivity and specificities of these techniques vary with 57% -74% sensitivity and 100% specificities reported for frozen section [3] [5], 63% sensitivity and 99% specificity for touch imprint cytology [6] and sensitivities of between 95% -98% with specificities of up to 97% for molecular assays [6]. Tests which utilise molecular assays use either reverse transcriptase polymerase chain reactions (RT-PCR) or reverse transcriptase loop-mediated isothermal amplifications (RT-LAMP).…”
Section: Introductionmentioning
confidence: 99%